N-[2-(6-Methyl-4-oxo-4H-chromen-3-yl)-4-oxothiazolidin-3-yl]furan-2-carboxamide N,N-dimethylformamide solvate - Pei-Liang Zhao; Zhong-Zhen Zhou (Acta Crystallographica Section E, 2009)
The title molecule, C18H14N2O5S·C3H7NO, comprises of a carboxamide group bonded to a furan ring and a distorted envelope-shaped 4-oxothiazolidin-3-yl group which is connected to a substituted 6-methyl-4-oxo-4H-chromen-3-yl group. Extensive strong N—H...O and weak C—H...O intermolecular hydrogen-bonding interactions occur between dimethylformamide (DMF), the crystallizing solvent, and the various heterocyclic groups within the compound, as well as additional weak C—H...O interactions between the heterocyclic groups themselves. The carboxyl group of the DMF solvent molecule forms a trifurcated (four-center) acceptor hydrogen-bond interaction with the carboxamide, furan and 6-methyl-4-oxo-4H-chromen-3-yl groups. The dihedral angles between the planar chromone group [maximum deviation = 0.0377 (18)°] and those of the furan and 4-oxothiazolidin-3-yl groups are 89.4 (6) and 78.5 (1)°, respectively.